The Longmire defense [compact disc, unabridged] - Johnson, Craig, 1961- (Johnson, Craig, 1961- Walt Longmire mystery., 2023)
Deep in the heart of the Wyoming countryside, Walt Longmire, sheriff of Absaroka County, is called to a crime scene like few others that he has seen. This crime will force him to confront the ghosts of his past, as his grandfather's past offers clues for Walt's investigation.